Application of the Shoutiyyah Method in Addressing Pronunciation Errors of Arabic Language Education Students at Universitas Negeri Makassar - Kudus, Ruhul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Pronunciation errors in reading Arabic texts remain a significant challenge for students in the Arabic Language Education Study Program at Universitas Negeri Makassar. These errors primarily involve difficulties in articulating specific Arabic letters, distinguishing between long and short vowels, and maintaining fluency while reading. Mispronunciations often lead to changes in meaning, which can hinder students' comprehension of texts, particularly in academic and religious contexts. To address these issues, this study aims to implement ath-thariqah as-shautiyyah as a phonetic-based teaching method to improve students' pronunciation accuracy in the Qiraah course. This research adopts a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation of students struggling with pronunciation. The analysis process involved data reduction, data presentation, and conclusion drawing to identify pronunciation errors and measure improvements following the implementation of ath-thariqah as-shautiyyah. The findings reveal that the method significantly enhances students’ ability to pronounce challenging Arabic letters, differentiate between short and long vowels, and read texts with greater fluency. The structured approach, which includes listening exercises, imitation, and systematic repetition, plays a crucial role in fostering phonological awareness. Additionally, students demonstrated increased confidence in reading Arabic texts aloud, indicating that the method also positively impacts their overall learning experience. In conclusion, ath-thariqah as-shautiyyah proves to be an effective strategy for overcoming pronunciation difficulties in Arabic reading instruction. Given its success in improving phonetic accuracy, fluency, and confidence, this method should be widely adopted in Qiraah courses.